2011
DOI: 10.1159/000330188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcimimetic Combined with an Angiotensin-Converting Enzyme Inhibitor on Uremic Cardiomyopathy Progression

Abstract: Background/Aims: Angiotensin-converting enzyme (ACE) inhibitors have cardioprotective properties and functional calcium-sensing receptors express in cardiac myocytes. Methods: Rats were made uremic by 5/6 nephrectomy and treated as follows: uremic rats were fed on a regular diet (UC), uremic + enalapril (E), uremic + calcimimetic agent R-568 (R-568), and uremic + enalapril + R-568 (E+R-568). A group of normal rats served as controls (NC). Results: Blood pressure (BP) and left ventricle mass were elevated signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…To our knowledge, this is the first report demonstrating uremic elevation of mACE-expression in relation to pro-atherogenic behaviour of primary human monocytes or THP-1 cells. Such a potential of ACE was previously reported in animal and cell culture models but was not directly correlated with influences of uremia on human monocytes in vitro [26], [27], [28], [29]. With regards to other cell culture systems, it has been demonstrated that uremic toxins may affect oxidative burst activity of the leukocytes and increase their pro-inflammatory effects.…”
Section: Discussionmentioning
confidence: 80%
“…To our knowledge, this is the first report demonstrating uremic elevation of mACE-expression in relation to pro-atherogenic behaviour of primary human monocytes or THP-1 cells. Such a potential of ACE was previously reported in animal and cell culture models but was not directly correlated with influences of uremia on human monocytes in vitro [26], [27], [28], [29]. With regards to other cell culture systems, it has been demonstrated that uremic toxins may affect oxidative burst activity of the leukocytes and increase their pro-inflammatory effects.…”
Section: Discussionmentioning
confidence: 80%
“…In the 5/6-nephrectomy rat model, treatment with the calcimimetic R-568 or enalapril improved cardiac fibrosis, and the effects were additive. 26 In a small study of patients receiving hemodialysis, treatment with cinacalcet improved diastolic dysfunction and reduced left ventricular mass index. 27 Second, cinacalcet may reduce cardiac and arterial calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Koleganova et al also observed lower TGF-b expression and TIMP-1 expression, restoration of MMP-1 expression and lower collagen type 1 and type 2 deposition that likely explain the observed prevention of fibrosis [134]. Recently, the ability of calcimimetics to attenuate cardiac fibrosis in uremic rats was enhanced with the concomitant administration of the angiotensin-converting enzyme inhibitor enalapril [135]. Both expression of factors associated with cardiac hypertrophy (proliferating cell nuclear antigen, cyclin D1 and cyclin D2) and cardiac fibrosis (type I collagen, fibronectin and TGF-b1) were attenuated with the calcimimetic R-568, enalapril and the combination of these drugs [135].…”
Section: Cardiomyopathymentioning
confidence: 97%
“…Recently, the ability of calcimimetics to attenuate cardiac fibrosis in uremic rats was enhanced with the concomitant administration of the angiotensin-converting enzyme inhibitor enalapril [135]. Both expression of factors associated with cardiac hypertrophy (proliferating cell nuclear antigen, cyclin D1 and cyclin D2) and cardiac fibrosis (type I collagen, fibronectin and TGF-b1) were attenuated with the calcimimetic R-568, enalapril and the combination of these drugs [135]. It is worth noting that, the CaSR is also actively expressed in rat cardiomyocytes [37,38].…”
Section: Cardiomyopathymentioning
confidence: 99%